2007
DOI: 10.1200/jco.2006.09.2437
|View full text |Cite
|
Sign up to set email alerts
|

Medical Oncologists' Views on Communicating With Patients About Chemotherapy Costs: A Pilot Survey

Abstract: There is important heterogeneity in medical oncologists' attitudes toward discussing chemotherapy treatment costs with patients. Mismatch between physician and patient viewpoints has the potential to result in miscommunication and suboptimally informed treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
136
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 18 publications
4
136
2
Order By: Relevance
“…Although, as is shown in some studies, 24 most oncologists think that they are aware of their patients' financial status, these data may refute such a perception of oncologists. Despite this, little is known about barriers to patient-oncologist communication in relation to the cost of care.…”
Section: Insurance Companies 11contrasting
confidence: 39%
See 2 more Smart Citations
“…Although, as is shown in some studies, 24 most oncologists think that they are aware of their patients' financial status, these data may refute such a perception of oncologists. Despite this, little is known about barriers to patient-oncologist communication in relation to the cost of care.…”
Section: Insurance Companies 11contrasting
confidence: 39%
“…Furthermore, 80% of respondents strongly agreed or agreed that "it is important to be explicit with patients about the financial consequences of treatment options. " 24 Likewise the results of a survey of 184 Australian oncologists showed that the price of cancer drugs influences their treatment recommendations. 25 Also, in a survey on 52 Israeli oncologists, 77% of them stated that inclusion of a cancer drug in the National List of Health Services influenced their treatment recommendations, and 92% believed that it affected their patients' access to treatment.…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…It becomes more difficult therefore to discuss these issues with patients in light of the fact that specific HCM medications may not be funded. In one US study, 84% of oncologists would mention treatment options to patients, even if they thought that the patient could not afford them [44]. In the context of that study, oncologists felt prepared to discuss all possible treatment options due to the fact that "out of pocket" copayments made by patients were commonplace.…”
Section: Patient-physician Relationshipmentioning
confidence: 99%
“…Physicians have been reported to discuss drug costs with patients [14,15,21,44]. The willingness to do so is dependent on the level of reimbursement of medicines within the health care system.…”
Section: Patient-physician Relationshipmentioning
confidence: 99%